2018
DOI: 10.3389/fphar.2018.01318
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of a TCM Formula Li-Ru-Kang in Rats With Hyperplasia of Mammary Gland and the Underlying Biological Mechanisms

Abstract: Li-Ru-Kang (LRK), a formula of eight traditional Chinese medicines (TCM), has been used to treat hyperplasia of mammary gland (HMG) in TCM clinics. However, how LRK works in HMG patients is unclear. To explore the possible mechanisms of LRK against HMG, the network pharmacology was used to screen the potential targets and possible pathways that involved in LRK treated HMG. Rat HMG model induced by estrogen and progesterone was used to further verify the effects of the key molecules of LRK selected from the enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The results showed that four targets (Gene names: AKT1 , EGFR , VEGFA and STAT3 ) were selected according to the following conditions: “Degree” value was twofold greater than the median value of all the network nodes (>16), “Betweenness centrality” value was greater than the median (>0.007), “Closeness centrality” value was greater than the median (>0.55) (J.‐B. Wang, Cui, et al, 2018; Y. Wang, Wei, et al, 2018). Therefore, AKT1, EGFR, VEGFA, and STAT3 might be the most important targets of CA‐BU in treating liver injury.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that four targets (Gene names: AKT1 , EGFR , VEGFA and STAT3 ) were selected according to the following conditions: “Degree” value was twofold greater than the median value of all the network nodes (>16), “Betweenness centrality” value was greater than the median (>0.007), “Closeness centrality” value was greater than the median (>0.55) (J.‐B. Wang, Cui, et al, 2018; Y. Wang, Wei, et al, 2018). Therefore, AKT1, EGFR, VEGFA, and STAT3 might be the most important targets of CA‐BU in treating liver injury.…”
Section: Resultsmentioning
confidence: 99%
“…To better elucidate the relationship between HZTF and gout, a compound-target-disease network was built with the protein-protein interaction (PPI) information, which was visualized and analyzed by Cytoscape v.2.5.1 (National Institute of General Medical Sciences, United States). The network topology parameters, including Degree, Betweenness Centrality, Average Shortest Path Length, and Closeness Centrality, were determined [ 29 ]. The degree of a node in the network indicates the number of nodes directly interacting with the node.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of bands was determined by densitometry analysis using TanonImagine. Data were normalized using β -actin (1 : 2000) (CST) as an internal control [ 29 ]. All experiments were performed in biological triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Oral bioavailability (OB) indicates the percentage of a drug being absorbed into the circulatory system and generates pharmacological effects after ingesting into the human body (33). The OB was calculated using the OBioavail 1.1 system and was set at a benchmark of ≥30% as OB less than 30% is regarded as low orally bioavailable drugs (34)(35)(36). The drug-likeness (DL) indicates the impression of a molecule's pharmacodynamics in the body and determines molecules with similar characteristics and targets.…”
Section: Screening For Bioactive Compoundsmentioning
confidence: 99%